Zika outbreak aftermath: status, progress, concerns and new insights. (5th July 2018) - Arora, Neelima; Banerjee, Amit K; Narasu, Mangamoori L
Zika, a neurotrophic virus belonging to Flaviviridae family of viruses and transmitted by vector mosquitoes of Aedes species, took the world by storm during its recent outbreak. Its spread to newer territories, unprecedented pace of transmission, lack of existing therapeutic agents and vaccines and an empty drug pipeline raised an alarm. Uncertainty about full spectrum of diseases and its long-term consequences, newly discovered modes of transmission and controversies over vector status of mosquito species like Culex quinquefasciatus led to layers of complexity and presented new hurdles and challenges in Zika virus research. This review summarizes the progress and updates of efforts, concerns, financial burden and available resources in light of newly acquired knowledge in Zika virus research.